Impact Assessment of Aqua Silviculture of Milagros and Placer, Masbate - Velza, Jacob Frederick P.; Ibañez, Roger Y.; Mahawan, Alvin M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
With the alarming poverty incidence among fisherfolks communities, the Department of Agriculture – Bureau of Fisheries and Aquatic Resources (DA-BFAR) embarked a project dubbed as Fisheries, Coastal Resources and Livelihood (FishCORAL) funded by United Nations International Fund for Agricultural Development (UN-IFAD) to address the problem by providing livelihood project to the coastal areas of different regions in the country. To assess the impact of the said project in the Bicol region, Bicol University in collaboration with different State Colleges and Universities in the region conducted a project called impact assessment on different project of the FishCORAL livelihood projects. The aim of the study is to assess the key indicators of the project if the goals of the project was met with the implementation of the livelihood project. The study used convenience sampling in the field surveys and focus group discussions to draw conclusion wherein the respondents are the recipient of the aqua silviculture livelihood project. The study reveals that the beneficiaries is under big household category making them hard to financially sustain the basic needs of the family because there is large percentage of dependent individuals. It was also noted that they do not have their own lot where they built their houses and the source of drinking water is unprotected well. In addition, the livelihood project is not sustainable because of various problems such as no profit from the first production cycle, most of the beneficiaries backed out during the implementation and the association itself is not technically prepared to implement the project to sustainable ends. Conduct of more technical capability training along varied aspects of aqua silviculture shall be caried out. Also, trainings on financial literacy, business management and basic record keeping are very necessary. There is also a need to craft a clearcut guideline and operational protocol to guide the aqua silviculture venture. Maybe, a root cause analysis of the previous production cycle should be carried-out to highlight lessons and undertake corrective measures. The association must be reorganized, reoriented and retooled.